Growth heterogeneity of Streptococcus suis in host-mimicking conditions is independent of clinical origin - Ayelén Perez-Falcón; Karl Kochanowski; Igor Florez-Sarasa; Elisenda Feixes-Prats; Florencia Correa-Fiz; Virginia Aragon (BMC Microbiology, 2026)
Abstract Background Streptococcus suis is an important swine and zoonotic pathogen whose virulence relies on complex, niche-specific metabolic adaptation within the host. However, the role of non-virulent S. suis strains in the host remains poorly understood. In this study, using host-mimicking media and biological fluids, we compared the growth of S. suis strains from different anatomical origins, including clinical isolates from diseased piglets and upper respiratory tract and vaginal isolates from healthy animals. Results Strains were evaluated in Todd-Hewitt Broth supplemented with yeast extract (THY), Human Plasma-Like Medium (HPLM), Synthetic Nasal Medium (SNM), and SNM supplemented with mucin (SNM + M). Most isolates exhibited robust growth in THY, whereas proliferation was reduced in HPLM and SNM. Notably, five isolates (two systemic, one nasal and two vaginal) displayed comparatively enhanced growth in SNM compared to the rest of the strains, although this phenotype was not associated with the anatomical origin of the strains. Mucin supplementation consistently increased growth across all tested isolates, suggesting that mucin availability may support S. suis proliferation under nutrient-limiting conditions. Experiments using biological fluids revealed that while all strains grew consistently in saliva, vaginal isolates showed comparatively reduced growth in vaginal fluid, indicating limited adaptation to this environment. No evidence of growth inhibition of virulent strains was observed during co-cultivation, while interactions were predominantly positive and influenced by nutrient availability. Conclusion In summary, S. suis displays strain-specific variability in growth under different in vivo-like conditions independently of clinical origin. These findings suggest a role of metabolic adaptation in shaping bacterial fitness and highlight the importance of using host‑mimicking environments to uncover phenotypic differences and interactions masked under standard laboratory conditions.